(untitled) (Abhat Journal, 2023)
The research aims to predict the maximum temperatures for the period (2021-2050). Depending on the maximum temperature of the Zuwara meteorological station for the base period (1961-1990) by ((Statistical Downscaling Model (SDSM)) technique, and used as data inputs HadCM3 model and climate change scenarios (A2a) (B2a), which are scenarios approved by the International Panel on Change IPCC in a report known as SRES in the year 2000 to develop forecasts for the climate and the environment based on greenhouse gases, in addition to relying on the statistical analysis methods used for climate data by the SPSS program to detect trends of change in the maximum temperatures for the three periods, namely: (1961-1990), (1991-2020), (2021-2050), and to achieve the objectives of the study, the homogeneity of the data and the variance of their averages were examined by means of the One Way ANOVA test, And the application of several statistical measures (standard deviation, accumulated differences), to serve as indicators for the analysis and identification of thermal extremes.The results showed a change in the annual and seasonal maximum temperature trends towards an increase compared to the first period and at a statistical significance level of less than 0.05. And the difference and variation in temperature extremes for the future period (2021-2050) at the quarterly level.